Estimation of Sodium Benzoate in Ayurvedic Formulation: Kashaya (Water Decoction) - BALACHANDRAN, S.; SUDHA DEVI, R. (Asian Journal of Chemistry, 2010)
Sodium benzoate, the food grade preservative, is the most commonly used preservative in kashaya-the water decoction of ayurvedic formulation. No standard procedure was known for the estimation of sodium benzoate in kashaya. The titrimetric estimation of benzoic acid using NaOH can be used as a standard method for its estimation. The amount of sodium benzoate observed in the commercial samples of nayopayam kashaya were many fold than that of maximum level allowed for food samples.